1986
DOI: 10.1090/s0002-9939-1986-0835893-x
|View full text |Cite
|
Sign up to set email alerts
|

A metric form of microtransitivity

Abstract: Abstract.We prove that every homogeneous compact metrizable space X has a compatible metric for which X is Lipschitz homogeneous and for which the group L( X) of Lipschitz homeomorphisms of X acts Lipschitz microtransitively on X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A. Hohti and H. Junnila [17] showed that every homogeneous locally compact separable metrizable space X is Lipschitz homogeneous. In the compact case, Hohti [16,Theorem 3.1] strengthened this result by showing that a homogeneous compact metrizable space X admits a metric ρ such that X is a coset space of L(X, ρ) in the compact-open topology.…”
Section: Theorem 11 ([30])mentioning
confidence: 99%
“…A. Hohti and H. Junnila [17] showed that every homogeneous locally compact separable metrizable space X is Lipschitz homogeneous. In the compact case, Hohti [16,Theorem 3.1] strengthened this result by showing that a homogeneous compact metrizable space X admits a metric ρ such that X is a coset space of L(X, ρ) in the compact-open topology.…”
Section: Theorem 11 ([30])mentioning
confidence: 99%
“…A. Hohti and H. Junnila [16] showed that every homogeneous locally compact separable metrizable space X is Lipschitz homogeneous. A. Hohti [15,Theorem 3.1] strengthened this result in a compact case showing that a compact metrizable X is a coset space of L(X, ρ) in the compact open topology for some metric ρ on X.…”
Section: Introductionmentioning
confidence: 95%